Det Identitetsløse Menneske Etter Modernismen Og Postmodernismen: Noen Eksempler Fra Nordisk Litteratur - Humpál, Martin (Folia Scandinavica Posnaniensia, 2012)
The author of this article attempts to show how the theme of lack of identity figures in Scandinavian literature of the recent decades, especially in postmodernism, and partially also later. The absence of identity was a considerably frequent theme in modernism. According to many modernists the lack of identity was characteristic of the people of the twentieth century, and modernists usually regarded this phenomenon as tragic. This changed in the 1960s. Some modernist writers of the 1960s began to view the absence of identity in a more conciliatory way: their works featured a greater acceptance for the idea of an individual with no core. This movement away from the tragic conception toward a greater acceptance forms an important line of development in later Scandinavian literature. The article discusses a few selected texts which illustrate this development. The examples include texts by Hans-Jørgen Nielsen, Dag Solstad, Peter Høeg and Erlend Loe.